2019
DOI: 10.1530/jme-18-0261
|View full text |Cite
|
Sign up to set email alerts
|

METTL7B promotes migration and invasion in thyroid cancer through epithelial-mesenchymal transition

Abstract: Thyroid cancer is associated with one of the most malignant endocrine tumors. However, molecular mechanisms underlying thyroid tumorigenesis and progression remain unclear. In order to investigate these mechanisms, we performed whole-transcriptome sequencing, which indicated that a differentially expressed gene, METTL7B, was highly expressed in thyroid cancers. We analyzed METTL7B expression using TCGA and performed qRT-PCR on tissue samples. Moreover, an analysis of clinicopathological characteristics reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…Previous study showed that METTL7B might serve as a biomarker for diagnosis and tumor progression in papillary thyroid carcinoma (Cai et al, 2018). METTL7B enhanced migration and invasion of thyroid carcinoma cells through promote TGF-b1-induced epithelial-mesenchymal transition (EMT) (Ye et al, 2019). In our study, we provide evidence showing that METTL7B is a potential therapeutic target for NSCLC.…”
Section: Discussionsupporting
confidence: 52%
“…Previous study showed that METTL7B might serve as a biomarker for diagnosis and tumor progression in papillary thyroid carcinoma (Cai et al, 2018). METTL7B enhanced migration and invasion of thyroid carcinoma cells through promote TGF-b1-induced epithelial-mesenchymal transition (EMT) (Ye et al, 2019). In our study, we provide evidence showing that METTL7B is a potential therapeutic target for NSCLC.…”
Section: Discussionsupporting
confidence: 52%
“…Endogenous thiols such as glutathione and cysteine or classic probe substrates of other known small molecule S -, N -, and O - methyltransferases were not substrates for METTL7B. Our results unequivocally demonstrate, and for the first time, that METTL7B, a protein implicated in several disease states, is an alkyl thiol methyltransferase(3–5). Identifying the catalytic function of METTL7B will enable future pharmacological research in disease pathophysiology where METTL7B expression and H 2 S levels can potentially alter the redox state and growth cycle of cells.…”
supporting
confidence: 49%
“…To date, the catalytic function of methyltransferase-like protein 7B (METTL7B) was unknown despite being implicated in several disease states. Specifically, METTL7B gene expression is significantly altered in kidney disease, acute respiratory distress syndrome, and numerous cancers, including breast, non-small cell lung, thyroid, and ovarian(3–5, 1417). METTL7B expression appears to be responsive to inflammation signaling pathways via JAK1(18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of non-small cell lung cancer (NSCLC), METTL7B is the target of NSCLC treatment and is involved in the regulation of the tumor cell cycle ( Liu et al, 2020 ). In addition, METTL7B may also activate TGFβ1 and induce EMT in thyroid cancer ( Ye et al, 2019 ). Our results also showed that METTL7B is highly expressed in both the metastasis group and the high-risk group, and is related to signaling pathways, such as the WNT and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%